An integral formula for L 2-eigenfunctions of a fourth-order Bessel-type differential operator - Kobayashi, Toshiyuki; Möllers, Jan (Integral Transforms and Special Functions, 2011)
We find an explicit integral formula for the eigenfunctions of a fourth-order differential operator against the kernel involving two Bessel functions. Our formula establishes the relation between K-types in two different realizations of the minimal representation of the indefinite orthogonal group, namely the L 2-model and the conformal model.